2016
DOI: 10.5853/jos.2016.00906
|View full text |Cite
|
Sign up to set email alerts
|

Direct Thrombus Imaging in Stroke

Abstract: There is an emergent need for imaging methods to better triage patients with acute stroke for tissue-plasminogen activator (tPA)-mediated thrombolysis or endovascular clot retrieval by directly visualizing the size and distribution of cerebral thromboemboli. Currently, magnetic resonance (MR) or computed tomography (CT) angiography visualizes the obstruction of blood flow within the vessel lumen rather than the thrombus itself. The present visualization method, which relies on observation of the dense artery s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 65 publications
0
38
0
Order By: Relevance
“…In addition, we have not been able to analyse thrombi retrieved after MT and therefore did not compare SVS and histology. However, published articles failed to find a reliable and reproducible association between the thrombi histology and recanalization results [ 10 , 36 ]. Indeed, there are inherent biases in assessing histologic characteristics of thrombi retrieved in vivo .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we have not been able to analyse thrombi retrieved after MT and therefore did not compare SVS and histology. However, published articles failed to find a reliable and reproducible association between the thrombi histology and recanalization results [ 10 , 36 ]. Indeed, there are inherent biases in assessing histologic characteristics of thrombi retrieved in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Thrombus composition could therefore be studied using the susceptibility vessel sign (SVS) on gradient recalled echo (GRE) sequences [ 9 ]. Intracranial clots are SVS-positive when red blood cells (RBCs) are predominantly present within the thrombus [ 8 , 10 - 12 ]. Retrospective and monocentric studies have shown that the qualitative evaluation of SVS could help predict recanalization and functional outcome after EVT [ 6 , 13 - 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent development in imaging technologies offers in vivo detection and observation of thrombus, such as magnetic resonance and computed tomography and ultrasound . However, these methods are insufficient for thrombus evaluation in small animals such as mice due to the relatively low resolution and the small vessel sizes .…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles including gold nanoparticles (AuNPs) and magnetic nanoparticles (MNPs) have been widely applied in the development of functional nanosystems for optical modulators [5,22], biosensors [23,24], imaging agents [25], and biological interfacing technology [26]. This suggests that complexation of the nanoparticles with responsive hydrogels allows the development of multipotent materials in a wide range of applications [27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%